Synergism of an Urgent Care Walk-in Clinic With an Emergency Department: A Pre-Post Comparative Study. - Bessert, B.; Oltrogge-Abiry, J. H.; Peters, P. S.; Schmalstieg-Bahr, K.; Bobardt-Hartshorn, J. S.; Pohontsch, N. J.; Bracht, S.; Mayer-Runge, U.; Scherer, M. (Deutsches Ärzteblatt International, 2023)
Background: The overutilization of hospital emergency departments by low-urgency patients is seen as a growing problem in healthcare delivery, and a variety of solutions are under discussion. We studied the change in utilization of a hospital emergency department (ED) by low-urgency patients after an urgent care walk-in clinic (WIC) was opened in the immediate vicinity. Methods: A prospective, single-center prepost comparative study was carried out at the University Medical Center Hamburg- Eppendorf (UKE). The ED patient collective consisted of adult walk-in patients who presented to the ED between 4 pm and midnight. The pre period consisted of August and September 2019, and the post period was from November 2019 (after the opening of the WIC) to January 2020. Results: The study patients consisted of 4765 ED walk-in patients and 1201 WIC patients. 956 (80.5%) of the WIC patients had been referred onward to the WIC after initially presenting to the ED; from this group, 790 patients (82.6%) received definitive care in the WIC. The number of outpatients treated in the ED fell by 37.3% (95% confidence interval [30.9; 43.8]), from 851.5 to 536.7 per month. The most marked decreases were in the areas of dermatology (from 62.5 to 14.3 patients per month), neurology (45.5 to 25), ophthalmology (115 to 64.7), and trauma surgery (211 to 128.7). No decrease was seen in urology, psychiatry, or gynecology. For patients presenting without any referral document, the mean length of stay fell by a mean of 17.6 [7.4; 27.8] minutes from its pre value of 172.3 minutes. The rate of patients who left during treatment fell from 76.5 to 28.3 patients per month (p <0.001). Conclusion: A GP-led urgent care walk-in clinic next door to an interdisciplinary hospital emergency department is a resource-saving treatment option for walk-in patients who present to the emergency department. Most of the patients referred from the ED to the WIC were able to receive definitive care there.